(untitled) (Revista Innova Educación, 2021)
The present study aims to analyze the academic contributions to the development of critical thinking in higher education students. The methodology used was a systematic review with descriptive level, using the PRISMA Statement method, using the search in the online databases of Scopus, EBSCO, ProQuest and ERIC. The review took into account the profile of the university teacher, didactic strategies and skills for the development of critical thinking and the appropriate context for its strengthening. Thirteen scientific articles were analyzed, of which 5 articles were of descriptive non-experimental design, 5 were quasi-experimental and 3 were of mixed design. It was concluded that the development of critical thinking is necessary in higher education, since it is considered an indispensable skill to face the challenges in a globalized world and also allows the teacher and the student to develop within a teaching-learning process that demands clarity, efficacy, precision and equity in problem solving.